100. Laterality indices determined by magnetoencephalography in three different temporal span may reflect better than one the complex reality of the language dominance. Issue 4 (April 2016) - Rossi Sebastiano, D.; Duran, D.; Visani, E.; Rotondi, F.; Canafoglia, L.; Panzica, F.; Franceschetti, S.
Abstract : In patients with medically intractable epilepsy or a brain tumor near the language areas, an important goal is to determine the language lateralization, to limit the risk of post-surgical language deficits. Our aim was to identify the hemispheric dominance and to localize the cortical activation during language tasks using magnetoencephalography (MEG). We applied a novel method for the language dominance testing in 10 patients candidates to neurosurgery, using three well known tasks: verb generation, word recognition, and picture naming. Source localization was performed using a MNE-based inverse model and the laterality index (LI) was calculated for each task using three different range intervals: 150–600 ms, 150–300 ms (prevalent Wernicke's activation) and 400–600 ms (prevalent Broca's activation). Data showed that there was a good consistence between the LIs and both fMRI and Edinburgh Handedness Inventory (80%). In particular, the Wernicke activation showed to be more appropriate for the LI calculation. Our results showed that MEG can be considered a reliable and non-invasive alternative to the Wada test.